Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found

Insidious incentives: A critical exercise to explore knowing, context, and multiple views. - Stepanovich, Paul L; Hopkins, Pamela J; Stark, Ernest (Management Teaching Review, 2017)
Keywords: dept.mgt